Sosialisasi 3 Dosa Besar Pendidikan untuk Membangun Karakter Anak Desa: Pengabdian - Septi Dwi Putri; Sarmila; Sri Eka Muliani; Nurmalasari; Nurazizah Amelia; Wardi; Yusrialdi; Arlin Saputra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) by students of Muhammadiyah University of Bone has implemented a socialization program regarding the Three Great Sins of Education (bullying, sexual violence, and intolerance) which aims to build children's character from an early age. This activity was held at SD Negeri 248 Gareccing, Gareccing Village, Tonra District, and involved around 60 students from grades 1 to 6. The method used was an interactive and educational approach adapted to the children's age, such as through stories, games, and group discussions to translate complex concepts into easy-to-understand language. The results of the activity showed high enthusiasm from the students, who actively participated and demonstrated an initial understanding of the importance of mutual respect, daring to say 'no' to unsafe touch, and celebrating differences. This socialization is an important first step in instilling positive character values ​​and creating a safe and inclusive school environment for children in rural areas.